Determinación de Valores Séricos y Factores Asociados en (canis familiaris) en el Barrio Macalo Chico, Macalo Grande y San Ramón. - Jácome Calero, Dayana Karina (2019)
The objective of this study is to determine serum values and associated factors of domestic dogs (from 0 to 12 months, 1 to 5 years and older than 5 years) in the Macaló Chico, Macaló Grande and San Ramón neighborhoods, through surveys and clinical files it was determined that the associated factors do influence the results of laboratory tests. This inductive and descriptive study determined in associated factors: 100% of canines have ample space, 97% come out 4 times or more times, 36% have a house, 76% are fed with homemade food, 56% are fed 3 times a day, 100% have water , 100% drink water from irrigation channels, 98% have been vaccinated against rabies and 2% have no vaccines, 41% live with cows and 59% with other animals, 100% of owners never collect the feces, 85% do not deworish them, 89% never take them to the veterinarian and 97% of the population has not seen coprophagia. The results of the tests sent to the laboratory were: Hematocrit: 8% high and 8% decreased, hemoglobin: 5% high and 8% decreased, erythrocytes: 3% high and 7% decreased, VGM: 4% high and 1% decreased, MCH 3% high and 1% decreased, CGMH: 12% decreased, platelets: 1% high and 21% decreased, leukocytes: 8% high and 5% decreased, neutrophils: 9% high and 5% decreased, N. Bands: 1% elevated, lymphocytes: 7% high and 5% decreased, Monocytes: 7% high and 1% decreased, Eosinophils: 12% high and 17% decreased and basophils 5% elevated. Glucose: 9% high, 12% decreased. In urea, 23% high, BUN: 19% high, 1% decreased. Creatinine: 23% high and 1% decreased, AST: 31% high. ALT 29% elevated. Total proteins: 3% high and 23% decreased.